Constructing Social Sanctions as a Preventive Strategy Against Sexual Violence in Indonesian Higher Education: A Mixed-Methods Study - Suardi, Suardi; Ramlan, Herdianty; Hashim , Shahrin Bin; Nursalam, Nursalam; Nur , Rahmat; Nur , Hasruddin (JED (Jurnal Etika Demokrasi), 2026)
Sexual violence in higher education remains a persistent structural problem that cannot be effectively mitigated through legal and bureaucratic mechanisms alone, especially in contexts where cultural and institutional norms inhibit reporting and accountability. This study aims to examine how members of an academic community construct and negotiate the meaning of social sanctions as preventive instruments against sexual violence on campus. Employing a sequential explanatory mixed-method design at Universitas Muhammadiyah Makassar, the research first conducted semi-structured qualitative interviews with students, faculty, and university leaders to explore shared understandings, moral reasoning, and perceived barriers surrounding social sanctions. These themes then informed the development of a quantitative survey, which was administered to a broader sample and analyzed using non-parametric statistical techniques. The findings reveal a strong consensus that social sanctions function as effective normative controls when they are applied consistently, transparently, and in ways perceived as procedurally just and morally legitimate by the campus community. Quantitative results further demonstrate significant positive associations between perceptions of consistent sanctioning by faculty and institutional leaders and the overall acceptance of social sanctions as a legitimate preventive mechanism. These results suggest that institutional integrity, value-based education, and participatory community engagement are critical for sustaining effective prevention of sexual violence. The novelty of this research lies in foregrounding socially constructed sanctions—rather than legalistic responses—as the central analytic lens in a Global South university context using a mixed-method approach. The study contributes conceptually and practically by offering an empirically grounded framework to guide universities and policymakers in designing community-based, value-driven strategies to prevent sexual violence on campus.